A Collaborative Study to Establish the Second International Standard for Streptokinase - Heath, A B; Gaffney, P J (Thrombosis and Haemostasis, 1990)
An International Standard for Streptokinase - Streptodomase (62/7) has been used to calibrate high purity clinical batches of SK since 1965. An international collaborative study, involving six laboratories, was undertaken to replace this standard with a high purity standard for SK. Two candidate preparations (88/826 and 88/824) were compared by a clot lysis assay with the current standard (62/7). Potencies of 671 i.u. and 461 i.u. were established for preparations A (88/826) and B (88/824), respectively.Either preparation appeared suitable to serve as a standard for SK. However, each ampoule of preparation A (88/826) contains a more appropriate amount of SK activity for potency testing, and is therefore preferred. Accelerated degradation tests indicate that preparation A (88/826) is very stable.The high purity streptokinase preparation, coded 88/826, has been established by the World Health Organisation as the 2nd International Standard for Streptokinase, with an assigned potency of 700 i.u. per ampoule.